The sensitizer 2,4-dinitrofluorobenzene activates caspase-3 and induces cell death in a skin dendritic cell line - Cruz, MT (2010)
In this work, a dendritic cell line derived from mouse skin (FSDC) was used, as an in vitro experimental model, to evaluate the cytotoxic effect of two chemical sensitizers, a strong sensitizer (2,4-dinitrofluorobenzene, DNFB) and a weak sensitizer (2,4-dichloronitrobenzene, DCNB). The results indicated that DNFB reduces the cellular metabolism of FSDC, as evaluated by the reduction of the tetrazolium salt, 3-(4,5-Dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide (MTT). All the DNFB concentrations tested, ranging from 5.2 micro M to 26 micro M, significantly inhibited the MTT reduction after 1 hour of cell exposure to the sensitizer. In contrast, incubation of FSDC with the weak sensitizer DCNB had no significant effect on the MTT reduction assay. When the cells were incubated with DNFB (13 micro M), for 3 and 6 hours, morphological changes characteristics of cell death by apoptosis were observed, as assessed by propidium iodide (PI) DNA staining and annexin-V externalization analysis. These results correlate well with an increase of caspase-3-like activity after FSDC exposure to DNFB (13 micro M) for 6 hours. Together, these results indicate that apoptotic death of skin dendritic cells occurs after exposure to the sensitizer DNFB, although necrotic cell death was also observed when the cells were incubated with high concentrations of DNFB (26 micro M), or after long periods of cell exposure to the chemical DNFB (13 micro M, for 6 hours).